3D cephalometric analysis using Magnetic Resonance Imaging: validation of accuracy and reproducibility - Jürchott, Alexander; Saleem, Muhammad Abdullah; Hilgenfeld, Tim; Freudlsperger, Christian; Zingler, Sebastian; Lux, Christopher J.; Bendszus, Martin; Heiland, Sabine (Scientific reports, 2018)
The aim of this study was to validate geometric accuracy and in vivo reproducibility of landmark-based cephalometric measurements using high-resolution 3D Magnetic Resonance Imaging (MRI) at 3 Tesla. For accuracy validation, 96 angular and 96 linear measurements were taken on a phantom in 3 different positions. In vivo MRI scans were performed on 3 volunteers in five head positions. For each in vivo scan, 27 landmarks were determined from which 19 angles and 26 distances were calculated. Statistical analysis was performed using Bland-Altman analysis, the two one-sided tests procedure and repeated measures one-way analysis of variance. In comparison to ground truth, all MRI-based phantom measurements showed statistical equivalence (p  0.05). Ranges between maximum and minimum in vivo values were consistently smaller than 2° and 2 mm, respectively (average ranges: 0.88°/0.87 mm). In conclusion, this study demonstrates that accurate and reproducible 3D cephalometric analysis can be performed without exposure to ionizing radiation using MRI.